Geomorphotectonic effects to determine the weathering front according to spectral reflectivity properties and visual interpretation of (RS) data for the southeastern slopes of Sinjar fold (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study is concerned with determining the prevailing type of weathering for thesoutheastern slopes of Mount Sinjar. Therefore, the use of remote sensing data tosolve this issue is one of the most important trends today. In order to employ (RS)data in this field, the researchers relied on soil moisture and temperature according tothe wavelength of each spot provided by the data of the American satellite (Landsat 8)and using modern computer software. Each type of surface component was sortedwith a specific wavelength according to its physical and chemical properties,following its moisture ratios, and then each type was given a specific weight, showingchemical weathering its dominance in this spot.